Students Competence Improvement in Fiction Writing Through Visual Symbol on Language Features Inovation - Nur Antoni Eko Tanuso; Januarius Mujiyanto; Dwi Anggani Linggar Bharati; Hendi Pratama (Universitas Negeri Semarang, 2021)
The study discovered that many students were still puzzled about the use of each tense and word order in writing fiction while teaching